Development of the CTL-based PPKn Module to Improve Student Learning Independence - Servista Bukit; Reh Bungana Perangin-angin; Abdul Murad (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to: (1) determine the feasibility of the CTL-based PPKn module; (2) determine the effectiveness of using the CTL-based PPKn module to increase student learning independence. This research is a development research with 4D models by Thiagarajan with four stages, namely Definition, Design, Development, and Disseminate. The trial design used was One Group Pretest-Posttest Design with sample of 25 students. The CTL-based PPKn module was declared very suitable to be used as a learning resource with the results of material expert validation by 90.63%, design expert validation by 93.75%, and linguist validation by 96.88%. The results of the N-Gain Score test are 0.72 so that the CTL-based PPKn module is effective for increasing student learning independence.